Clinical trial evaluating the effectiveness of biocompound IMMUNEPOTENT CRP in the third-molar extraction - Franco Molina, Moisés Armides; Mendoza Gamboa, Edgar; Coronado Cerda, Erika Evangelina; Zárate Triviño, Diana Ginette; Arizpe Coronado, Juan E.; Zapata Benavides, Pablo; Ramos Zayas, Yareellys; Tamez Guerra, Reyes Silvestre; Rodríguez Padilla, Cristina (2016)
ABSTRACT A controlled, parallel, randomized and comparative trial was carried out to evaluate the antiinflammatory efficacy of IMMUNEPOTENT CRP versus ibuprofen in patients after third-molar surgery over seven days. The anti-inflammatory efficacy of IMMUNEPOTENT CRP was evaluated using the method of Amin and Laskin, and the analysis of cytokine production (IL-2, IL-4, IL-6, IL-10, TNF-a, INF-g) in saliva was done by flow cytometry. The swelling process after surgery was significant (p < 0.05) and the treatments with IMMUNEPOTENT CRP or ibuprofen controlled this process properly; no difference between the groups was found (p < 0.05). Both treatments were shown to modulate the cytokine production. These results demonstrate the anti-inflammatory activity of the natural compound IMMUNEPOTENT CRP and suggest it could be used in clinical dental practice.